Local Infiltration Analgesia for Postoperative Pain Control following Skin Crease “Bikini Incision” Anterior Total Hip Arthroplasty for Neglected Femoral Neck Fractures: A Double-Blinded Randomized Control Trial - Lorena, Angelico Gabriel; Baron, Joel (Philippine Journal of Orthopaedics, 2025)
Background. The incidence of femoral neck fractures continues to increase along with the rise of the elderly population, and in the Philippines, a significant number have become neglected. Total hip arthroplasty (THA) is the treatment of choice for previously healthy and active patients. Local infiltration analgesia is a known adjunct for postoperative pain control, but its effects for THA via the “bikini incision” anterior approach are yet to be established. Objective. The study primarily aims to determine the effectiveness of local infiltration anesthesia using bupivacaine (as compared to placebo) in reducing acute post-operative pain in adult patients who have undergone THA for a neglected femoral neck fracture via the skin crease “bikini incision” anterior approach. Methodology. Forty-two patients (21 per treatment arm) aged 50–80 who underwent THA via the said approach were included in a double-blinded randomized control trial (RCT). Modified d’Aubigné-Postel score, pain control on the first two postoperative days, and length of hospital stay were the measured outcomes. Independent Sample T-test, Mann-Whitney U test, and Fisher’s exact/Chi-square test were used to determine the differences in mean, rank, and frequency, respectively, between the two groups. Null hypotheses were rejected at 0.05 α-level of significance. Result. On postoperative day one, the local infiltration anesthesia group had a higher Modified d’Aubigné-Postel median score compared to the placebo group (14 vs. 12, p = 0.026). Day one median NRS was also slightly lower versus the placebo group (3 vs. 4, p = 0.032). On day two, NRS scores decreased for both groups, and the difference between the groups was not statistically significant (1 vs. 2, p = 0.203). The number of rescue doses on both days and the length of hospital stay were not significantly different for both groups. No adverse effects were recorded. Conclusion. Statistically, local infiltration anesthesia reduces pain only on day one after THA via the anterior “bikini incision” approach for neglected femoral neck fractures. However, clinically, no significant differences in functional and pain scores were observed between the groups. Therefore, local infiltration anesthesia cannot be routinely recommended for post-operative pain management in this population.